Predictors of hospitalization plus airway support among infants with recurrent wheezing in the emergency department (2021)
ABSTRACT: Objective: Most patients with recurrent wheezing are infants under 2 years of age. Clinical prediction models of the risk of receiving airway support during the hospital stay in this population have been poorly studied in tropical countries. This study aimed to evaluate the clinical predictors of hospitalization plus airway support among infants with recurrent wheezing evaluated in the emergency department in Colombia. Methods: A retrospective cohort study was performed. This study included all infants with two or more wheezing episodes who were younger than two years old in two tertiary centers in Rionegro, Colombia, between January 2019 and December 2019. The primary outcome measure was hospitalization plus any airway support. A multivariable logistic regression model was used to identify factors independently associated with hospitalization plus any airway support. Results: A total of 85 infants were hospitalized plus any airway support, of whom 34(40%) were treated with high flow nasal canula, 2(2%) received non-invasive ventilation, 6(7%) were mechanically ventilated, and 43 (51%) received conventional oxygen therapy. The multivariable logistic regression model showed that predictors of hospitalization plus airway support included prematurity (OR=1.79, 95%CI: 1.04-3.10), poor feeding (OR=2.22, 95%CI: 1.25-3.94), nasal flaring and/or grunting (OR=4.27, 95%CI: 2.41-7.56), and previous wheezing episodes requiring hospitalization (OR=3.36, 95%CI: 1.86-7.08). The model has a high specificity (99.6%) with acceptable discrimination and an area under the curve of 0.70(95%CI: 0.60-0.74). Conclusions: The present study shows that prematurity, poor feeding, nasal flaring and/or grunting, and more than one previous episode of wheezing requiring hospitalization are independent predictors of hospitalization plus airway support in a population of infants with recurrent wheezing in the emergency department. More evidence must be collected to examine the results in other tropical countries.